Land And Building Tax Capabilities In Escalating Regional Original Income - Misbahul Aulia; Selmita Paranoan; Chalarce Totanan; Muhammad Iqbal (UNIVED Press, 2025)
This research aims to analyze the capability of Land and Building Tax (PBB) in increasing Local Own-Source Revenue (PAD) in Donggala Regency. This research employs a quantitative approach with descriptive and analytical designs. The data used are PBB and PAD data for the last five years, from 2019 to 2023, obtained from the Regional Revenue Agency of Donggala Regency. The research results indicate that the potential of PBB in Donggala Regency has not been optimal, with a negative potential percentage in 2023. The effectiveness of PBB collection during the research period shows fluctuations, with the best performance in 2019 and 2021, but experiencing a significant decrease in 2022. This research concludes that the regional government needs to implement various strategic efforts to enhance the capability of PBB, such as updating tax object data, improving technology-based administrative services, and providing education to the public. It is expected that increasing the capability of PBB can provide a more significant contribution to PAD and support sustainable regional development.